The Forms of Medieval Agrarian Colonisation: Contributions from Law and Geography (Edad Media. Revista de Historia, 2019)
This article underscores the possibilities of renovating the study of agrarian colonisation in the Middle Ages by taking advantage of the juridical framework of analysis contributed by ‘agrarian law’ and the geographical model contributed by planimetries. Its main tenet is that agrarian colonisation brings with it the legal definition of those spaces falling outside the scope of ordinary law. For some of these, certain planned spatial morphologies may be identified, two of whose types are dealt with here: ‘medieval centuriation’ and the coaxial division. In the end, all throughout the Middle Ages and its main periods, a great juridical and morphological creativity is revealed.
Keywords: Agrarian Colonisation; Agrarian Law; Land Concession; Medieval Centuriation; Coaxial land division; Agrarian Morphology; Fiscal Land; Prisia; Populatio